2022
DOI: 10.1523/jneurosci.1199-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Computer Model of the Spinal Dorsal Horn Reveals Changes in Network Processing Associated with Chronic Pain

Abstract: Pain-related sensory input is processed in the spinal cord before being relayed to the brain. That processing profoundly influences whether stimuli are correctly or incorrectly perceived as painful.Significant advances have been made in identifying the types of excitatory and inhibitory neurons that comprise the spinal dorsal horn (SDH), and there is some information about how neuron types are connected, but it remains unclear how the overall circuit processes sensory input. To explore SDH circuit function, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 126 publications
1
35
0
Order By: Relevance
“…NetPyNE (Dura-Bernal et al, 2019 ) is a high-level declarative NEURON wrapper used to develop a wide range of neural circuit models (Metzner et al, 2020 ; Anwar et al, 2021 ; Bryson et al, 2021 ; Pimentel et al, 2021 ; Ranieri et al, 2021 ; Romaro et al, 2021 ; Volk et al, 2021 ; Borges et al, 2022 ; Dura-Bernal et al, 2022a , b ; Medlock et al, 2022 ) 4 , and also as a resource for teaching neurobiology and computational neuroscience.…”
Section: Methodsmentioning
confidence: 99%
“…NetPyNE (Dura-Bernal et al, 2019 ) is a high-level declarative NEURON wrapper used to develop a wide range of neural circuit models (Metzner et al, 2020 ; Anwar et al, 2021 ; Bryson et al, 2021 ; Pimentel et al, 2021 ; Ranieri et al, 2021 ; Romaro et al, 2021 ; Volk et al, 2021 ; Borges et al, 2022 ; Dura-Bernal et al, 2022a , b ; Medlock et al, 2022 ) 4 , and also as a resource for teaching neurobiology and computational neuroscience.…”
Section: Methodsmentioning
confidence: 99%
“…Degeneracy can be found not only at the single cell level but also at the network level of synaptically connected neurons. Analogous to multiple configurations of intrinsic ion channels leading to indistinguishable electrical behavior of single neurons (Taylor et al, 2009), multiple configurations of synaptic properties can support indistinguishable electrical behavior of neuronal networks (Prinz et al, 2004;Marder and Goaillard, 2006;Medlock et al, 2022;Narayanan, 2019, 2021b). Moreover, the circuit degeneracy is also enhanced by the fact that intrinsic and synaptic channels can (not only in isolation but also) jointly con-tribute to indistinguishable network activity (Prinz et al, 2004;Marder and Goaillard, 2006;Grashow et al, 2010).…”
Section: Degenerate Synaptic (And Intrinsic) Propertiesmentioning
confidence: 99%
“…A simulation study of the thalamo-cortical network in childhood absence epilepsy (Knox et al, 2018) Another recent multiscale simulation study, although not focusing on epilepsy, has provided novel insights on degeneracy in the context of pathological perturbations linked to hyperexcitability associated with chronic pain (Medlock et al, 2022). In network simulations of spinal dorsal horn, the authors have demonstrated that, under physiological conditions, similar circuit activity can emerge in different models with disparate configurations of synaptic properties.…”
Section: Similar Lfp and Eeg Discharges Despite Diversity Of Underlyi...mentioning
confidence: 99%
“…Our findings are in agreement with a general and increasingly accepted concept of degeneracy (Edelman and Gally, 2001). In complex degenerate systems, such as the nervous system, multiple distinct mechanisms can be sufficient, but typically not necessary, to account for a given function or malfunction, such as normal excitability or hyperexcitability (Kamaleddin, 2022; see also Neymotin et al ., 2016; Ratté and Prescott, 2016; O’Leary, 2018; Medlock et al ., 2022). Consistent with the degeneracy framework, our results suggest that multiple extrinsic and intrinsic mechanisms are sufficient but not necessary to increase neuronal excitability in AD.…”
Section: Discussionmentioning
confidence: 99%